Analisa Pretasi Laporan Keungan Pada PT Ginting Jaya Tbk Pariode Tahun 2019-2021 - Nia Ramadani Putri Mulia; putri pilmela; indah afriliani putri (CV. ITTC INDONESIA, 2025)
period 2019 to 2021 from the perspectives of management, shareholders, and creditors. A descriptive method was employed, utilizing financial ratio analysis including profitability, liquidity, solvency, operational efficiency, and working capital management. The data were obtained from the company’s annual financial reports officially published during the study period. The results show that from a managerial perspective, the company experienced a significant decline in operational performance, as indicated by increasing expense ratios, decreasing gross profit margins, and a sharp drop in contribution to net sales. Asset turnover remained low, and working capital management was suboptimal. From the shareholders’ perspective, profitability deteriorated, with negative earnings per share and no dividend distribution for three consecutive years, reflecting poor returns on equity. From the creditor’s point of view, the company maintained a relatively good current ratio, but the declining quick ratio and negative interest coverage over two years raise concerns regarding solvency and debt repayment capability.